Improvements in Jump Height, Speed, and Quality of Life through an 8-Week Strength Program in Male Adolescents Soccer Players - Sara Díaz-Hidalgo; Antonio Ranchal-Sanchez; Jose Manuel Jurado-Castro (MDPI AG, 2024)
This study aimed to assess the enhancement of physical fitness and quality of life through an 8-week strength training program in male adolescent soccer players aged between 12 and 13 years. A lower body muscle group intervention was performed, with 17 players in the experimental group (EG) and 15 players in the control group (CG). The EG carried out soccer training complemented by specific strength work. Pre- and post- intervention assessments included body composition, jump height, speed with change of direction, maximum speed in 20 m, movement velocity in back-squat, perceived fatigue effort, academic performance, and quality of life. A general linear repeated measures model analysis was used considering each variable, the interaction between groups (EG, CG) and time (basal, 8-week), to analyze the differences between and within groups. The results showed a reduction in fat in the upper limbs and trunk, improvements in jump height, maximum speed of 20 m, and changes of direction, and increased quality of life (p < 0.05) in the EG. It was concluded that a strength program could improve some components of physical performance in male adolescent soccer players.